The role of compliance in promoting equality between men and women in the workplace - Carrilho Bernardineli, Muriana; Grasiella Silvério, Mayara; Renata Capelesso, Karen (Revista Chilena de Derecho del Trabajo y de la Seguridad Social, 2024)
Despite women being the majority in the labor market, studies indicate that they still do not significantly occupy management and leadership positions. Women face high rates of sexual and moral harassment, precarious positions, salary inequality and other forms of discrimination, even though they have equal or higher qualifications than men. This research aims to analyze compliance as a tool combined with corporate management, with the purpose of reducing and preventing discriminatory practices and gender-based violence, seeking to promote a more inclusive, fair, respectful, safe and egalitarian work environment. The methodology used was bibliographical review and research, deductive method and historical analysis, which helped to develop the research.